2000
DOI: 10.1111/1468-0351.00058
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Economic Factors and Equity Markets in Central Europe

Abstract: This paper investigates the possibility that newly-emerging equity markets in Central Europe exhibit semi-strong form efficiency such that no relationship exists between lagged values of changes in economic variables and changes in equity prices. We find that while there are connections between the real economy and equity market returns in Poland and Hungary, these links occur with lags, suggesting the possibility of profitable trading strategies based on public information and rejecting semi-strong efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…We will review below part of this literature devoted to the Central and Eastern European countries gradually recovering market economy after the communist past. Hanousek and Filer (2000) find in 1993-1999 almost no contemporaneous relation between stock returns in Poland, Hungary, and the Czech Republic and macroeconomic variables; yet demonstrate that these variables had predictive ability in the first two countries, interpreting this as a rejection of the semi-strong efficiency. Sokalska (2001) argues that comovement of equity indices in the Czech Republic, Hungary, and Poland in 1993-2000 may be due to the common shocks in the "international investor sentiment."…”
Section: Introductionmentioning
confidence: 78%
“…We will review below part of this literature devoted to the Central and Eastern European countries gradually recovering market economy after the communist past. Hanousek and Filer (2000) find in 1993-1999 almost no contemporaneous relation between stock returns in Poland, Hungary, and the Czech Republic and macroeconomic variables; yet demonstrate that these variables had predictive ability in the first two countries, interpreting this as a rejection of the semi-strong efficiency. Sokalska (2001) argues that comovement of equity indices in the Czech Republic, Hungary, and Poland in 1993-2000 may be due to the common shocks in the "international investor sentiment."…”
Section: Introductionmentioning
confidence: 78%
“…A second strand in literature points out that financial development follows economic growth. Hanousek & Filer (1997) determined that, among ex-communist countries (The Czech Republic, Hungary, Poland and Slovakia), the Czech equity market is characterized by semi-strong efficiency. However, while for the other three, changes in the real economy affect the stock exchange parameters with a lag of 1; therefore, they do not present this form of efficiency, and there is sufficient space for opportunity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hanousek and Filer [10] revealed that based on the contemporaneous or lagged values, Poland's stock index is not correlated with the U.S. DJIA or German DAX. Wang and Moore [11] found significant correlation between the stock markets in the Czech Republic, Hungary Poland and the eurozone market during and after the financial crises.…”
Section: Literature Surveymentioning
confidence: 99%